Potencial antibacteriano do óleo essencial de Croton tetradenius (Baill.) frente a bactérias uropatógenas e sinergismo com antibióticos - Siqueira, Ingrid Borges (2017)
Urinary tract infections (UTIs) are the most common infections experienced by humans. It is mainly found in the female gender and it is generally associated with symptomatic and asymptomatic bacteriuria. The most commom etiological agent of UTIs is Escherichia coli (approximately 90% of cases); However, other Gram-negative and some Gram-positive bacterias may be involved in the infectious process. Facing the current scenario of antibiotic resistant strains selection, the study of alternative methods for the control of infectious diseases has been the object of several research groups. Therefore, the purpose of this work was to test different genotypes of Croton tetradenius essential oil (EO) against strains of Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae and Pseudomonas aeruginosa. Initially, the spectrum of the oils activity against these microorganisms was tested by the agar diffusion method. In order to evaluate the antimicrobial activity, the Minimal Inhibitory Concentration (MIC) and Minimum Bactericidal Dose (MBD) of the oils against the selected strains were determined followed by a test to determine the microorganisms growth curve. The Checkboard Method was used to evaluate the synergism between the essential oils and the antibiotics ciprofloxacin and meropenem against the bacterias used. The cytotoxicity of the essential oils was verified by the MTT method (3- (4,5-dimethylthiazol-2-il) -2,5-diphenyltetrazolium bromide), against mouse fibroblast lineage L929. Then it was observed that C. tetradenius genotypes showed activity against the tested microorganisms. In addition, the inhibition halos found higher than 9 mm and the only microorganism that was not inhibited by any of the genotypes was P. aeruginosa. Also the MIC for the microorganisms tested ranged from 1.4 to 11.3 mg / mL, while the MBD varied from 2.8 mg / mL to 11.3 mg / mL. By increasing the concentration of essential oil in the culture medium the lag phase raised while the growth rate decreased as well as the maximal DO reached by cultures. Essential oils in combination with antibiotics showed a synergistic effect in most combinations, being indifferent only to E.coli when combined with EO and ciprofloxacin. The tested oils had no cytotoxicity at concentrations of 50 and 100 ug / ml.